2012
DOI: 10.1039/c1cp22324k
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of density functional theory for bonds formed between rare gases and open-shell atoms: a computational study of small molecules containing He, Ar, Kr and Xe

Abstract: The validity of the description of the DFT approximations currently implemented in plane wave DFT codes (LDA, GGA, meta-GGA, hybrid, GGA + empirical dispersion correction) for interactions between rare gases and open-shell atoms which form materials is poorly known. We have performed a first assessment of the accuracy of these functionals for the description of the bonds formed by helium, argon, krypton and xenon with various open-shell atoms. This evaluation has been done on model molecular systems for which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…This effect, which has a dominant contribution in the chemical interaction involving rare gas elements, is expected to be more important for the lightest (He) than for the heaviest (Xe) atom as a consequence of the largest polarizability of the heaviest atoms. 74 The so-called DFT-D2 Grimme approach, 75 which consists in adding a semiempirical dispersion potential to the conventional Kohn-Sham DFT energy and the van der Waals density functional (vdW-DF) approach 76 which considers the nonlocal interaction as a density-density interaction, are available in the recent release of the VASP code (version 5.2) in order to estimate the van der Waals interactions in a solid. An earlier version of VASP is used in this study, so the van der Waals contributions could not be estimated precisely.…”
Section: Other Inert Gas Incorporationmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect, which has a dominant contribution in the chemical interaction involving rare gas elements, is expected to be more important for the lightest (He) than for the heaviest (Xe) atom as a consequence of the largest polarizability of the heaviest atoms. 74 The so-called DFT-D2 Grimme approach, 75 which consists in adding a semiempirical dispersion potential to the conventional Kohn-Sham DFT energy and the van der Waals density functional (vdW-DF) approach 76 which considers the nonlocal interaction as a density-density interaction, are available in the recent release of the VASP code (version 5.2) in order to estimate the van der Waals interactions in a solid. An earlier version of VASP is used in this study, so the van der Waals contributions could not be estimated precisely.…”
Section: Other Inert Gas Incorporationmentioning
confidence: 99%
“…At the phenomenological level, in a UO 2 crystal, Gryaznov et al 77 mentioned a van der Waals contribution of −0.25 eV to the He incorporation energy, taking into account a posteriori shell-model empirical potentials. Moreover, Bertolus et al 74 showed that, for the incorporation of rare gases in small molecules such as HeHCN and KrHCN, a relative error of several percent was found on their binding energy. In our case, the incorporation energies of helium are about several eV with a minimum of 1.13 eV for the I He V Ti case.…”
Section: Other Inert Gas Incorporationmentioning
confidence: 99%
“…The validity of several types of functionals for the description of bonds formed by rare gases has also been assessed on model molecular compounds [37]. The results show that when the rare gas atom shares density with the neighbouring atoms, the GGA functionals yield good geometries and qualitatively correct binding energies, even if these are quite significantly overestimated.…”
Section: Assessment Of Atomic Scale Methods For the Description Of Bumentioning
confidence: 99%
“…2,3 Among various noble gases, less attention has been made on the first two noble gases, helium and neon and some studies have been focused on the chemistry of argon [4][5][6] and krypton. [7][8][9][10] Since preparation, isolation and study of noble gas compounds are difficult, theoretical methods have been mostly used to anticipate the bonding, 11,12 formation 13 and properties 14,15 of these compounds. Some investigations have been focused on the theoretical study of all noble gases without considering a special noble gas.…”
Section: Introductionmentioning
confidence: 99%
“…38 In addition, the preparation and reactivity of compounds containing a carbon-xenon bond have been reviewed by Frohn. 39 Contrary to the large number of experimental and theoretical studies on organoxenons, [40][41][42][43][44][45][46][47][48][49] many potential molecules and their properties in this area are also unknown and research on the new organoxenon compounds seems to be interesting. One of them is the effect of counter ions on the stabilities and properties of organoxenon cations.…”
Section: Introductionmentioning
confidence: 99%